2021
DOI: 10.1038/s41598-021-81922-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a peritumoral pseudocapsule in patients with renal cell carcinoma undergoing robot-assisted partial nephrectomy using enhanced MDCT

Abstract: To investigate the detection of peritumoral pseudocapsule (PC) using multi-detector row computed tomography (MDCT) for tumors resected by robot-assisted laparoscopic partial nephrectomy (RAPN) for T1 renal cell carcinoma (RCC). Study participants included 206 patients with clinical T1 RCC who underwent RAPN between October 2017 and February 2018. Two radiologists who were blinded to the pathological findings evaluated the computed tomography (CT) images. Radiological diagnosis of a PC was defined by a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
1
8
2
Order By: Relevance
“…However, pPS thickness and vasculature of TPI were associated with ctPS that ctPS-absent tumors had drastically thinner pPS and enriched vessels (long diameter ≥ 200 um). In a recent study comparing ctPS and pPS, the authors found that the accuracy of ctPS is not satisfactory even with 64- or 320-detector MDCT, 15 which could be explained by our results that whether there is a pPS is not the most important fundamental structure of a ctPS. The finding was interesting.…”
Section: Discussioncontrasting
confidence: 59%
“…However, pPS thickness and vasculature of TPI were associated with ctPS that ctPS-absent tumors had drastically thinner pPS and enriched vessels (long diameter ≥ 200 um). In a recent study comparing ctPS and pPS, the authors found that the accuracy of ctPS is not satisfactory even with 64- or 320-detector MDCT, 15 which could be explained by our results that whether there is a pPS is not the most important fundamental structure of a ctPS. The finding was interesting.…”
Section: Discussioncontrasting
confidence: 59%
“…ChRCC is associated with relatively good prognosis, and a high proportion of PC absence 3,9 . In our study, PC was absent in 5 (42%) out of 12 ChRCCs, a proportion that was slightly lower than the previously reported (47%–70%) 5,9,14 . The risk of PC absence was significantly greater when the tumor diameter was less than 34 mm in stage T1 RCC 9 .…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies reported that CCRCC was associated with tougher and thicker PC composed of higher collagen fiber density compared with PC in non‐CCRCC 6,21 . This may explain why some surgeons hold the view that TE is not suitable for non‐CCRCC patients 9,14,21 . Peritumoral PC is the natural surgical dissection plane for TE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Insufficient preparation activities 1998 is another epoch-making mark in the development of CT technology [6]. In this year, several major CT equipment manufacturers simultaneously launched four layer acquisition spiral CT (multislice spiral CT), and its principle has been introduced in other literatures [7]. Taking this as a starting point, the 8-layer spiral CT was launched in 2000.…”
Section: Literature Reviewmentioning
confidence: 99%